Institutions, policy reforms and efficiency in new member states from Centraland Eastern Europe - Štefan Bojnec; Imre Fertő; Attila Jámbor; József Tóth (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
This paper investigates determinants of agricultural sector efficiency in ten new member states (NMS-10) of the European Union (EU) from Central and Eastern European countries by the non-parametric method Data Envelopment Analysis (DEA) and the panel data analysis. The agricultural sector efficiency varies between the NMS-10. We have found positive and significant association of the agricultural sector efficiency with the natural agricultural factor endowments, average farm size, farm specialization, small-scale farms, and the EU integration process. The foreign direct investments have an ambiguous affect, while the nominal assistance rate is not found significant. Reform and institutional developments and liberalization are associated with the agricultural sector efficiency positively, and vice versa infrastructure development and agricultural policy reforms, which have caused job flows and agricultural employment adjustments. The urban-rural income gap with job flows and agricultural labour adjustments have caused the agricultural sector efficiency positively.
Keywords: C14; C23; Q12; 330; agricultural efficiency; institutions; policy reforms